Difusi Inovasi UMKM Kampung Lele Melalui Program Gesari Binaan PT Semen Jawa - Fildzah Berliana Ramadhani; Heni Hayat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Innovation in the Micro, Small, and Medium Enterprises (MSMEs) sector plays a crucial role in increasing competitiveness and strengthening the sustainability of local economies in Indonesia. This study aims to analyze the diffusion process of catfish floss product innovation in Kampung Lele MSMEs in Sukamaju Village, Sukabumi Regency, through the Independent Village Movement (Gesari) Program, supported by PT Semen Jawa. The study employed a qualitative descriptive method, with data collection techniques involving in-depth interviews with business owners and related parties. Based on Rogers' diffusion of innovation theory, the results indicate that the catfish floss innovation can increase the added value of fresh catfish, create employment opportunities for the surrounding community, and support stunting prevention efforts through diversification of highly nutritious fish foods. This innovation is considered to have relative advantages, a high level of welfare relative to the community's socioeconomic conditions, and ease of adoption, although it still faces several obstacles such as limited market access and digital technology. This study recommends the need for expanded digital marketing and ongoing training for MSMEs to ensure the continued development of the innovation. These findings contribute to strengthening community empowerment policies and the development of MSMEs based on local potential.